What makes online teaching spatial? Examining the connections between K-12 teachers’ spatial skills, affect, and their use of spatial pedagogy during remote instruction - Kelsey Rocha; Catherine M. Lussier; Kinnari Atit (Cognitive Research, 2022)
Abstract Spatial skills are critical for student success in K-12 STEM education. Teachers’ spatial skills and feelings about completing spatial tasks influence students’ spatial and STEM learning at both the primary and secondary levels. However, whether spatial skills and spatial anxiety differ or not between these two teacher levels is unknown. Additionally, the relations between teachers’ spatial skills, spatial anxiety, and their use of spatial pedagogical practices in remote learning settings is unknown. Here, we investigated if spatial skills and spatial anxiety differ between teachers working at primary versus secondary levels, and examined the relations between their spatial skills and spatial anxiety while accounting for additional influential factors—general reasoning ability and general anxiety. Lastly, we investigated how teachers’ spatial skills in conjunction with their spatial anxiety relate to their use of spatial teaching practices for online instruction. Sixty-two K-12 teachers completed measures of spatial skills, spatial anxiety, general anxiety, general reasoning, and a teaching activities questionnaire. Results indicate that spatial skills and spatial anxiety may not vary between teachers working at primary versus secondary levels, but that higher spatial skills in teachers are associated with lower spatial anxiety for mental manipulation tasks. Additionally, teachers with weaker spatial skills and lower mental manipulation anxiety reported more frequently using spatial teaching practices when teaching remotely due to COVID-19. These findings may have broad implications for teacher professional development with regards to developing students’ spatial skills during remote learning.